A Turn into Film Narration: Contemporary Video Game Narration on the Example of The Last of Us Series - Kossakowski, Mateusz (Media - Culture - Social Communication, 2021)
Over the years, video games have evolved considerably ‒ from less complicated productions based on simple mechanisms to big-budget, complex creations. Along with the technical development of games, their creators have also started to pay closer attention to their narrative layer. This has led to using the term “immersion,” which comes from psychological and literary studies measuring gamer perception. The narration in games is not the same narration known from other traditional media. Here, a gamer, using the constructed game mechanics and making (linear or non-linear) choices, creates his/her own story. Without such engagement in the gameplay, it is impossible to fully experience the story. These immersive elements can be seen in many single-player games, which in the narration appears increasingly cinematic in its narrative style, as exemplified by Naughty Dogʼs The Last of Us. The series is set in a post-apocalyptic United States. Among other things, character personalities, dialogues, the complexity of the created world and certain measures taken to enrich the plot allow the series to trigger strong emotions. The criticsʼ reviews attest to this – The Last of Us and its sequel have been nominated for Game of the Year multiple times, and their average ratings, according to GameRankings and Metacritic, place them among the best-rated video games ever. In this article, the author attempts to analyse the plot and key mechanics of the series to show the journey that video games have gone through from their inception to modern narrative forms and tries to answer the question of what ultimately made The Last of Us series one of the best-selling new brands in the history of the PlayStation console.